1100 Self-Monitoring Of PVT Performance In Healthy Adults And Individuals With MDD. (27th May 2020) - Galli, O; Goel, N; Basner, M; Detre, J; Thase, M; Sheline, Y; Rao, H; Dinges, D; Gehrman, P
Abstract: Introduction: Negativity bias in depression has been repeatedly demonstrated in the judgment and decision-making literature. Research investigating the impact of sleep deprivation on self-evaluation of performance in healthy or depressed populations is limited. We examined 1) whether individuals with Major Depressive Disorder (MDD) exhibit a negativity bias in subjective ratings of performance on the Psychomotor Vigilance Task (PVT) as compared with healthy adults, and 2) the impact of total sleep deprivation (TSD) on these ratings. Methods: N=33 individuals with MDD and n=9 healthy adults completed a 5-day study protocol including two baseline nights (B1-B2, 9h TIB), 36 hours of TSD, and one night of recovery sleep opportunity (Rec). The PVT was administered every 2-4 hours. A brief questionnaire was administered immediately prior to (PRE) and following (POST) the PVT, asking participants to estimate their average reaction time (RT) using a 9-point Likert-type scale. Mixed-effects models examined the impact of group (MDD, Control), protocol day (B1, B2, SD, Rec), and their interaction on objective PVT performance (mean RT) and subjective performance estimates (PRE and POST ratings). Results: Mean RT was significantly slower during TSD (p<0.001) for all participants. Individuals with MDD and healthy adults did not differ in objective PVT performance (p=0.25) across days. There was no significant interaction between group and protocol day (p=0.96). Both groups predicted slower RTs during TSD as compared with baseline or recovery days (PRE-PVT, p=0.006). Individuals with MDD anticipated slower RTs as compared with healthy adults (p=0.001). On POST-PVT estimates, all participants reported subjective poorer performance during TSD (p<0.008). Individuals with MDD reported slower RTs as compared with healthy adults (p=0.002). Interaction effects between group and protocol day on PRE- and POST- performance ratings were not significant. Conclusion: This project is the first to investigate subjective estimates of PVT performance in healthy and depressed individuals. Individuals with MDD subjectively reported slower response times as compared with control participants, despite similar objective performance. Depressive symptoms may be a potential confounder of subjective, but not objective, PVT performance. Support: 5R01MH107571